PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS 3 MELALUI PENGGUNAAN MEDIA DADU PADA MATERI PENYAJIAN DATA - Ilham Nur Fadli; Widia Nur Jannah; Dewi Yuningsih; Mulyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the learning outcomes of third-grade students at SDN Kemakmuran II in mathematics, specifically on the topic of data presentation, through the use of dice as a learning medium. Based on preliminary observations, it was found that students' understanding of data presentation concepts was still low, as indicated by learning outcomes that had not yet met the minimum mastery criteria. This study employed a Classroom Action Research approach, conducted over two cycles. The results showed that the use of dice media effectively improved student learning outcomes, as evidenced by an increase in the average student score from 72 in the first cycle to 84 in the second cycle, and an increase in the percentage of learning mastery from 67.86% to 85.70%. The use of dice media was able to create an enjoyable learning atmosphere and enhance student participation in the learning process.